2016
DOI: 10.1039/c6dt00309e
|View full text |Cite
|
Sign up to set email alerts
|

Solvent influence on the thermodynamics for hydride transfer from bis(diphosphine) complexes of nickel

Abstract: The thermodynamic hydricity of a metal hydride can vary considerably between solvents. This parameter can be used to determine the favourability of a hydride-transfer reaction, such as the reaction between a metal hydride and CO2 to produce formate. Because the hydricities of these species do not vary consistently between solvents, reactions that are thermodynamically unfavourable in one solvent can be favourable in others. The hydricity of a water-soluble, bis-phosphine nickel hydride complex was compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 47 publications
0
61
0
Order By: Relevance
“…Neither the Ni nor Rh systems have been examined in water at this time. The vast majority of hydricity measurements, in general, have been performed in acetonitrile solution, but some aqueous studies have been reported recently. ,, Based on the small data set of available aqueous hydricities, switching from acetonitrile to water can significantly increase hydride donating abilities (lower Δ G H– ). Similar to acidity scales in organic versus aqueous solution, the range of accessible hydricities narrows in higher polarity solvents like water, but the hydricities do not change linearly due to different relative stabilizations of hydride species between the two solvents, different specific interactions with the solvent (e.g., hydrogen bonding), and the relative energies of the M-aqua versus M-acetonitrile complex (for cases where the parent metal complex is solvated).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Neither the Ni nor Rh systems have been examined in water at this time. The vast majority of hydricity measurements, in general, have been performed in acetonitrile solution, but some aqueous studies have been reported recently. ,, Based on the small data set of available aqueous hydricities, switching from acetonitrile to water can significantly increase hydride donating abilities (lower Δ G H– ). Similar to acidity scales in organic versus aqueous solution, the range of accessible hydricities narrows in higher polarity solvents like water, but the hydricities do not change linearly due to different relative stabilizations of hydride species between the two solvents, different specific interactions with the solvent (e.g., hydrogen bonding), and the relative energies of the M-aqua versus M-acetonitrile complex (for cases where the parent metal complex is solvated).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…45,46 The small difference in hydricity relative to transition metal hydride complexes has been exploited for solvent-dependent CO 2 reduction reactions. 4,6,7,13,14 The small solvent dependent hydricity of formate has previously been attributed to Hbonding stabilization of HCO 2 − . 7 Equation 1 reveals that the CO 2 being a gas phase hydride acceptor is also an important, previously unrecognized factor.…”
Section: ■ Introductionmentioning
confidence: 99%
“…2 The different relative hydricities of metal complexes and small molecules in different solvents have been exploited for significant advances in the field of CO 2 reduction, where a hydride transfer that is uphill in acetonitrile can become thermodynamically favorable in water. 4,6,7,13,14 A quantitative understanding of how thermodynamic hydricity will change across solvents and the factors that determine the relative hydricity of hydride donors in each solvent has been lacking. Deeper conceptual and quantitative insights into the influence of solvent on hydricity would provide more predictive power and new opportunities for applications in catalyst design.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, a simple change of solvent altered the mechanism through modulation of thermodynamic hydricity, and thereby, resulted in efficient aqueous‐phase CO 2 ‐hydrogenation catalysis in the presence of a mild bicarbonate base. Appel and co‐workers reported a similar study on how to drive the conversion of CO 2 to formate just by switching the solvent [14a] . The ΔGH-0 value of the formate anion (HCO 2 − ) in CH 3 CN was found to be 44 kcal mol −1 .…”
Section: Role Of Hydricity In Exploring and Optimizing An Alternativementioning
confidence: 92%
“…Very few Ni catalysts are known that are both very good hydride donors to CO 2 and efficient for easy catalytic liberation of CO 2 ‐reduction products. Notably, by applying a ligand‐tuning strategy, Appel and co‐workers developed moderately efficient Ni catalysts for aqueous‐phase CO 2 hydrogenation under mild‐base conditions, as discussed earlier [14a, 36] . However, Lu and co‐workers explored a different concept, in which they sought to stabilize the Ni−H complex in a more electron‐rich environment, yet allowing facile regeneration of Ni−H from H 2 and base.…”
Section: Role Of Hydricity In Exploring and Optimizing An Alternative Energy Schemementioning
confidence: 99%